Implementasi Metode Waterfall Pada Sistem Informasi Stock Opname - Oky Irnawati (Indonesian Journal on Software Engineering (IJSE), 2018)
ABSTRACT - Technology development change system management which was originally to be done manually be computerized. Benefits of systems that are considered to be managed in a computerized can benefit the company is no exception PT. Setiajaya Mobilindo. In managing the system supplies parts PT .Setiajaya Mobilindo have used technology information using desktop based program. But there are still the problem in system that runs of them were not the availability of programs to perform stock opname, Making it difficult to seeing how goods in the warehouse with data on database, the absence of a program to see a groove out of making it difficult to find the transaction goods Based on the discussion mentioned above then the researcher want to provide solutions by improving program was with the waterfall, start from analysis software needs , design , encoding , until testing. Improvement of the program will start from planning system to the stages of the design of detailed system , includes the design of a database , the design of control , the design of output input, until the technology. is expected that improvement program that has been there would be produced program to suit the needs of users and can to be the solution for the existing problems now. Keywords: Stock Opname Information System